Intelligent automated computer systems - Zakovorotniy, A.; Kharchenko, Artem (ISMA University of Applied Science, 2021)
Fuzzy logic and neural network methods are currently used to solve problems related to process modeling in the conditions of uncertainty or insufficient input data. Neural networks allow not only to model processes as close as possible to real ones, but also to forecast the values of technical parameters. The reliability of a computer system depends on the right choice of the input parameters and the accuracy of calculations. This work is devoted to the issue of developing the automated computer system, taking into account the dynamics of railway vehicles.
Keywords: computer systems; fuzzy logic; neural network; intelligent control; forecasting